2015
DOI: 10.1039/c5cc03734d
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation of the sodiation process in CuO nanowires

Abstract: In situ transmission electron microscopy was used to observe the dynamic evolution of the morphology and phase transformations in CuO nanowires during the process of sodiation. Our results facilitate a fundamental understanding of the sodiation mechanism in CuO nanostructures used as electrode materials in sodium ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 34 publications
(50 reference statements)
0
36
0
Order By: Relevance
“…The electrochemical reaction that occurs at the interface is an essential process during battery operation, and the kinetics of the reaction front plays a decisive role in governing the rate performance of batteries . Recently, the lithiation and the sodiation processes of CuO nanowires were studied by taking the advantage of in situ transmission electron microscopy (TEM) . Golberg et al.…”
Section: Figurementioning
confidence: 99%
“…The electrochemical reaction that occurs at the interface is an essential process during battery operation, and the kinetics of the reaction front plays a decisive role in governing the rate performance of batteries . Recently, the lithiation and the sodiation processes of CuO nanowires were studied by taking the advantage of in situ transmission electron microscopy (TEM) . Golberg et al.…”
Section: Figurementioning
confidence: 99%
“…[ 397 ] In the in situ TEM measurement, CuO nanowires and Na metal were used as the working and counter electrodes, respectively. A mixture of Na 2 O and NaOH that was naturally grown on a Na metal surface was used as the solid electrolyte (Figure 15 d).…”
Section: (26 Of 38)mentioning
confidence: 99%
“…A few strategies were proposed including molecular tuning of the mother structure, surface coating, and polymerization. [ 266,389,394,397,[454][455][456][457][458]461,465 ] Several biomolecule-based organic compounds were also investigated as potential organic anodes for NIBs. [459][460][461] Luo et al demonstrated that coroanic acid disodium salt (CADS) is capable of delivering 246.7 mA h g −1 of capacity at the voltage range of 0.7 to 2.0 V vs Na + /Na, however, the capacity of the CADS electrode rapidly faded because of the volume change during phase transformation.…”
Section: Organic Anodesmentioning
confidence: 99%
“…Additionally, the W tip was moved carefully to contacted the CuO−Pt NW presented in Figure e again, and thus an electric potential was applied to the CuO−Pt NW. The potential increased gradually and was cut off once the Pt NPs started to merge (see the insets in Figure a and 4b).…”
Section: Resultsmentioning
confidence: 99%